Analysis of the Selection of Birth Aid in Lebiti Village, Togean District, Tojo Una-Una Regency - Nur Afni Imbran; Sitti Nur Djannah; Solikhah Solikhah (Universitas Aisyah Pringsewu, 2021)
Ensuring that maternal deliveries are assisted by trained health personnel such as midwives, doctors or nurses who have been educated and trained to master the appropriate skills to manage normal pregnancy and the puerperium, are able to identify management and make referrals for complications to mothers and newborns is one of the efforts to reduce maternal and newborn mortality and morbidity. This study aims to determine in-depth the determinants that influence pregnant women in choosing birth attendants. Using this type of qualitative research, with in-depth interviews and observations. The informants in this study were 6 mothers who had given birth, 1 village midwife, and 1 non-medical worker (traditional birth attendant). The results of interviews conducted showed that the mother's decision in choosing birth attendants was influenced by knowledge, culture, traditional birth attendant services and access to health care facilities that were quite far away. Abstrak: Memastikan persalinan ibu ditolong oleh tenaga kesehatan terlatih seperti bidan, dokter atau perawat yang telah dididik dan dilatih untuk menguasai keterampilan yang tepat untuk mengelola kehamilan normal dan nifas, mampu mengidentifikasi manajemen dan membuat rujukan komplikasi kepada ibu dan bayi baru lahir. merupakan salah satu upaya untuk menurunkan angka kematian dan kesakitan ibu dan bayi baru lahir. Penelitian ini bertujuan untuk mengetahui secara mendalam determinan yang mempengaruhi ibu hamil dalam memilih penolong persalinan. Menggunakan jenis penelitian kualitatif, dengan wawancara mendalam dan observasi. Informan dalam penelitian ini adalah 6 ibu bersalin, 1 bidan desa, dan 1 tenaga non medis (dukun bersalin). Hasil wawancara yang dilakukan menunjukkan bahwa keputusan ibu dalam memilih penolong persalinan dipengaruhi oleh pengetahuan, budaya, pelayanan dukun bayi dan akses ke fasilitas pelayanan kesehatan yang cukup jauh.